2015
DOI: 10.1186/s13012-016-0482-7
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of multifaceted implementation strategies for the implementation of back and neck pain guidelines in health care: a systematic review

Abstract: BackgroundFor the optimal use of clinical guidelines in daily practice, mere distribution of guidelines and materials is not enough, and active implementation is needed. This review investigated the effectiveness of multifaceted implementation strategies compared to minimal, single, or no implementation strategy for the implementation of non-specific low back and/or neck pain guidelines in health care.MethodsThe following electronic databases were searched from inception to June 1, 2015: MEDLINE, Embase, PsycI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 64 publications
(40 reference statements)
3
39
0
Order By: Relevance
“…In a systematic review of the implementation interventions designed to improve clinical practice for the management of LBP in low back pain Mesner et al [33] found that a range of interventions had been applied but that single, one-off strategies were consistently unsuccessful and there was no consistent pattern with regards the differential effectiveness of the different types of implementation events utilised. Suman et al [34] systematically reviewed the evidence of the effectiveness of multifaceted guideline implementation strategies for back and neck pain and did not find consistent benefits when they were compared to either usual or minimal intervention. Mesner et al [33] concluded that frequency of messaging may be important as ongoing and regular interventions demonstrated greater success in changing practice and sustaining those changes, but advise caution on the basis of between study heterogeneity and risk of bias in the included literature.…”
Section: The Challenge Of Implementationmentioning
confidence: 99%
“…In a systematic review of the implementation interventions designed to improve clinical practice for the management of LBP in low back pain Mesner et al [33] found that a range of interventions had been applied but that single, one-off strategies were consistently unsuccessful and there was no consistent pattern with regards the differential effectiveness of the different types of implementation events utilised. Suman et al [34] systematically reviewed the evidence of the effectiveness of multifaceted guideline implementation strategies for back and neck pain and did not find consistent benefits when they were compared to either usual or minimal intervention. Mesner et al [33] concluded that frequency of messaging may be important as ongoing and regular interventions demonstrated greater success in changing practice and sustaining those changes, but advise caution on the basis of between study heterogeneity and risk of bias in the included literature.…”
Section: The Challenge Of Implementationmentioning
confidence: 99%
“…Many guideline groups that have sought to involve stakeholders have utilized limited numbers of participants or utilized slow and labor-intensive processes (e.g., time and resources needed to administer, collate, and respond to over 200 stakeholder views and comments) [12]. It is recognized that successful guideline development and implementation requires the engagement of multiple stakeholders [24] and "shared solutions" (input from patients, clinicians, and policymakers) improve health outcomes [24][25][26]. Patient/public stakeholders may potentially feel intimidated to contribute if they are only one voice among many.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the current study are in line with other studies that have attempted to improve patient outcomes and costs in LBP by using multifaceted strategies. A systematic review of the effectiveness of multifaceted strategies for guideline implementation in LBP and neck pain did not find that multifaceted strategies changed patient outcomes or costs of care 45. However, the majority of the studies included in the review did not provide insight into the implementation process, raising the question whether the lack of effectiveness is caused by the failure of the theory (multifaceted strategy) or by failure of the implementation process, making it difficult to compare the current study to others.…”
Section: Discussionmentioning
confidence: 99%